Uang Panai: Between Tradition And Perception Among Bugis, Moronene, And Sundanese Culture In Indonesia - Sain, Yuliyanah; Sanhas, Tasman; Nufus, Siti Hayatun; R, Novita P; Amin, Syarif (Universitas Pahlawan Tuanku Tambusai, 2025)
The